Analysis of the new requirements on Warehouse Management System in logistic operation - Tokarev, Mikhail; Jirsák, Petr; Rathouský, Bedřich; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This research aims to give insight into the current requirements on Warehouse Management System implementation in logistic operation. Providing the methodology of the research, elaborating on the findings of the research and the implications of those findings for managers working in Logistics. Overall, the brief overview on Warehouse Management Systems are covered as well as the analysis of the new trends in Warehouse Management Systems implementation will be gone over along with how they affect the new requirements of WMS implementation in Logistics.
Vedoucí práce: Petr Jirsák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses